2020
DOI: 10.1016/j.annepidem.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and lifetime adverse maternal outcomes (gestational diabetes and hypertensive disorders of pregnancy) in the Hispanic Community Health Study/Study of Latinos

Abstract: Purpose: Childhood adversity is associated with increased risk of adult disease, including type 2 diabetes and hypertension. However, little is known about potential associations between childhood adversity and adverse pregnancy outcomes. The goal of this study is to examine the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…15 Prior studies (Appendix 1, available online at http://links.lww.com/AOG/C460) that have examined this relationship are limited by small sample sizes, 13 populations with limited generalizability, 16,17 or significant concern for confounding bias. [18][19][20] To fill this evidence gap, our objective was to examine the association between adverse childhood experiences and adverse perinatal outcomes using a diverse sample of individuals with perinatal mental health conditions. We hypothesized that having a high ACE (adverse childhood experience) score would be associated with an increased prevalence of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…15 Prior studies (Appendix 1, available online at http://links.lww.com/AOG/C460) that have examined this relationship are limited by small sample sizes, 13 populations with limited generalizability, 16,17 or significant concern for confounding bias. [18][19][20] To fill this evidence gap, our objective was to examine the association between adverse childhood experiences and adverse perinatal outcomes using a diverse sample of individuals with perinatal mental health conditions. We hypothesized that having a high ACE (adverse childhood experience) score would be associated with an increased prevalence of adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…These studies are also limited by small sample sizes, with childhood adversity measured through retrospective reporting of adversities that is prone to recall bias. [10][11][12] Research reporting an association found that those who experienced childhood physical or sexual abuse had the greatest risk of developing GDM, with several other adversity types left unaccounted for. 13,14 Other adversities occurring in childhood have previously been found to affect health outcomes including type 2 diabetes, 15 and studies show that family and social adversity are highly entangled and cannot be understood independently of each other.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified a link between childhood adversity and the risk of developing GDM, though studies are few and report mixed findings. These studies are also limited by small sample sizes, with childhood adversity measured through retrospective reporting of adversities that is prone to recall bias 10–12 . Research reporting an association found that those who experienced childhood physical or sexual abuse had the greatest risk of developing GDM, with several other adversity types left unaccounted for 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…As pregnancy is a natural stress test for the future development of chronic disease, groups at high risk of diabetes, that is, women with multiple ACEs, are more likely to develop HIP. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…As pregnancy is a natural stress test for the future development of chronic disease, groups at high risk of diabetes, that is, women with multiple ACEs, are more likely to develop HIP. [6,7] Poor parent-daughter relationships can be one phenotype of ACEs, as poor parent-child relationships were also associated with youth smoking, unhealthy weight control behavior, obesity, and psychological distress in adulthood [8][9][10]. Thus, the pregnant women's relationship with their parents may be associated with HIP risk.…”
Section: Introductionmentioning
confidence: 99%